2014
DOI: 10.1158/1535-7163.mct-13-0482
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Genomic Alterations between Primary and Recurrent Breast Cancer

Abstract: There is growing interest in delivering genomically-informed cancer therapy. Our aim was to determine the concordance of genomic alterations between primary and recurrent breast cancer. Targeted next generation sequencing was performed on formalin-fixed paraffin embedded (FFPE) samples, profiling 3320 exons of 182 cancer-related genes plus 37 introns from 14 genes often rearranged in cancer. Point mutations, indels, copy number alterations and select rearrangements were assessed in 74 tumors from 43 patients (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 24 publications
(29 reference statements)
11
72
0
Order By: Relevance
“…Collectively, there is increasing evidence that the mutation analysis results for cfDNA are highly concordant with those for archival tumor tissue for concordantly, but not discordantly, collected samples, which may be explained by tumor biology, including heterogeneity and evolution over time [10,21]. In addition, our KRAS G12/G13 multiplex assay detects seven of the most frequent KRAS G12/G13 mutations in one reaction; in other PCR approaches, this would require seven separate tests.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Collectively, there is increasing evidence that the mutation analysis results for cfDNA are highly concordant with those for archival tumor tissue for concordantly, but not discordantly, collected samples, which may be explained by tumor biology, including heterogeneity and evolution over time [10,21]. In addition, our KRAS G12/G13 multiplex assay detects seven of the most frequent KRAS G12/G13 mutations in one reaction; in other PCR approaches, this would require seven separate tests.…”
Section: Discussionmentioning
confidence: 85%
“…Also, mutation status can change over time, and discrepancies between the genomic profiles of primary and metastatic tumors may occur [9][10][11]. Thus, archival FFPE tumor samples, which may be many years old, might not necessarily reflect the pertinent genotype.…”
Section: Introductionmentioning
confidence: 99%
“…However, the agreement rate is lower if the samples are obtained at different times, which may be explained by tumor heterogeneity and evolution over time. For instance, one such study showed that only 97 of 112 (86.6%) somatic mutations were concordant between 33 matched primary and metastatic breast cancers (9).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BRAF mutation analysis is not feasible in up to 50% of patients with ErdheimChester histiocytosis (7). Finally, mutation status can change over time, and discrepancies between the genomic profiles of primary and metastatic tumor sites have been reported (8,9). Thus, archival FFPE tumor samples, which may be many years old, might not necessarily reflect the pertinent genotype.…”
Section: Brafmentioning
confidence: 99%
“…For the remaining four cases, CGP was performed on a different specimen, including one case where the samples were collected at the same time, but from different sites, and another case where hotspot testing was performed on a sample with low cellularity and reported a negative result, prompting the treating physician to request that another sample be collected and submitted for CGP. In general, oncogenic drivers have been demonstrated to be highly concordant in primary and metastatic biopsies across a variety of tumor types (14)(15)(16)(17). Explanation of the discordance between hotspot results and CGP observed here awaits further analysis.…”
Section: Discussionmentioning
confidence: 66%